(untitled) (Journal of Rashid Latif Medical College, 2023)
Objective: The aim of the study was to determine the frequency of different musculoskeletal symptoms among salt mine workers ofPakistan.Methodology: 61 salt-mine workers were approached in this cross sectional survey using convenient sampling. The datawas collected using NORDIC questionnaire. The data was entered and analyzed using SPSS 25. Association between different risk factors like age, duration of working etc. and body pain were determined using likelihood ratio.Results: Among the workers 5(8.2%) have Full Body pain, 23(37.7%) have pain in Neck, 5(8.2%) have pain in Shoulder, 8(13.1%) have pain Arm, 9(14.8%) have pain in Upper Back, 2(3.3%) have pain in Lower Back, 7(11.5%) have pain in Legs, 1(1.6%) has pain in Knees and one has pain in Foot. Overall 12.1% workers have history of not going to work dueto pain.Conclusion: Whole body vibration has adverse effect on body specifically on neck, shoulder and arm region among salt mine workers. Age of operator, duration of working has also significant impact on pain.Key words: Musculoskeletal pain. salt mine workers, whole body vibration